2010
DOI: 10.1002/jbmr.266
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3α/β inhibition promotes in vivo amplification of endogenous mesenchymal progenitors with osteogenic and adipogenic potential and their differentiation to the osteogenic lineage

Abstract: Small molecules are attractive therapeutics to amplify and direct differentiation of stem cells. They also can be used to understand the regulation of their fate by interfering with specific signaling pathways. Mesenchymal stem cells (MSCs) have the potential to proliferate and differentiate into several cell types, including osteoblasts. Activation of canonical Wnt signaling by inhibition of glycogen synthase kinase 3 (GSK-3) has been shown to enhance bone mass, possibly by involving a number of mechanisms ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…Another study demonstrated the abrogation of glucocorticoid-induced bone loss by the GSK3␤ inhibitor 6-bromoindirubin-3Ј-oxim (77). Furthermore, the novel GSK3␤ inhibitor AR28 induced ␤-catenin nuclear translocation and increased bone mass after 2 wk, possibly due to an amplification of mesenchymal stem cells that became osteoblasts at the expense of adipocytes (78).…”
Section: Lithium and Gsk3␤ Inhibitorsmentioning
confidence: 97%
“…Another study demonstrated the abrogation of glucocorticoid-induced bone loss by the GSK3␤ inhibitor 6-bromoindirubin-3Ј-oxim (77). Furthermore, the novel GSK3␤ inhibitor AR28 induced ␤-catenin nuclear translocation and increased bone mass after 2 wk, possibly due to an amplification of mesenchymal stem cells that became osteoblasts at the expense of adipocytes (78).…”
Section: Lithium and Gsk3␤ Inhibitorsmentioning
confidence: 97%
“…In vitro deletion of the b-catenin gene significantly reversed the increased ALP activity observed in Axis inhibition protein 2 knockout bone marrow stromal cells [20]. Whereas induced b-catenin nuclear translocation was shown to enhance bone mass in BALB/c mice [21]. Furthermore, inhibition of p38 MAPK could interrupt canonical Wnt/b-catenin signaling, and attenuate the Wnt3a-induced b-catenin accumulation [22].…”
Section: Discussionmentioning
confidence: 96%
“…Progeroid syndromes and particularly DS are an invaluable model to determine the molecular markers predisposing to stem cell aging and are suitable to unveil new molecular targets for chemical intervention. Identification of compounds which can be used to manipulate stem cells for therapeutic purposes is well underway with proof-ofconcept approaches in small molecule manipulation of both ES cells and adult tissue stem/progenitor cells (Gambardella et al 2011;Sato et al 2004;Chen et al 2006;Trowbridge et al 2006). These early studies points to interesting times for progeroid syndromes, stem cell biology and aging research.…”
Section: Discussionmentioning
confidence: 97%